Cultural Intelligence as a Predictor of Psychological Adjustment among Expatriate Faculty Members at University of Hail - Al-Shammari سعود بن عايد (Dirasat: Human and Social Sciences, 2023)
Objectives: Study aimed to identify the level of cultural intelligence as a predictor of degree of psychological adjustment among expatriate faculty members at University of Hail. Methods: The descriptive method was used. The study tools were two Cultural intelligence scales (score 20- 60), and psychological adjustment scale (score 30- 90). A convenient sample that consisted of (132) members out of the (501) expatriate faculty members at University of Hail was selected. Results: The study found a high level of cultural intelligence and psychological adjustment among expatriate faculty members at University of Hail, and a positive statistically significant relationship at level of significance (0.01) between cultural intelligence and its sub-dimensions (metacognitive - cognitive - motivation - behavior) and total degree of psychological adjustment. Results of regression analysis revealed that cultural intelligence predicted adjustment, as two dimensions (motivation, and metacognitive) were able to contribute together to predicting (73.2%) of psychological adjustment. There were no statistically significant differences in cultural intelligence, as well as psychological adjustment among expatriate faculty members due to academic degree, length of stay in Saudi Arabia, nationality, college, age, and gender. Conclusions: Cultural intelligence has a predictive ability to psychological adjustment among expatriate faculty members at University of Hail, specifically motivation and meta-cognitive dimensions.